Assessment of biomarkers of oxidative stress in doves exposed to neonicotinoid-treated soybean cotyledons - Addy Orduna, Laura; Cazenave, Jimena; Mateo, Rafael (Facultad de Humanidades y Ciencias, Universidad Nacional del Litoral, 2024)
Póster